Do we have something in common? Understanding national identities through a metanarrative analysis. Issue 4 (1st September 2022) - Kaplan, Yael R.; Sheafer, Tamir; Shenhav, Shaul R.
Abstract: Many scholars stress the role national identities play as an essential element that shapes interests and explains political behaviours. Others, however, contend that national identities are too amorphic and highlight the analytical challenge of employing them as a research variable. We propose the use of metanarratives as a theoretical framework that captures the essence of national identities and allows the comparative study of their similarities and differences. Metanarratives are shared dominant stories that guide values, beliefs and behaviours and help communities understand who they are. We develop a new systematic method for measuring their content and present a three‐step process for gauging metanarratives. We demonstrate this method on 159 countries, analysing constitution preambles to assess each nation's metanarrative and create a global identity orientation map. We show how this approach enables the classification and comparison of national identities and discuss its potential contribution to further empiric study of national identities.